High-resolution view of active tectonic deformation along the Hikurangi subduction margin and the Taupo Volcanic Zone, New Zealand. Issue 1 (2nd January 2016) - Dimitrova, LL; Wallace, LM; Haines, AJ; Williams, CA
ABSTRACT: Understanding the mechanisms and dynamics of deformation at plate boundaries requires high-resolution images of strain and deformation sources. Vertical derivatives of horizontal stress (VDoHS) rates are the horizontal-component surface manifestation of all subsurface deformation sources, and have substantially higher spatial resolution than GPS velocities or strain rates. We calculate VDoHS rates from GPS data at the Hikurangi subduction margin. We evaluate our results in the context of interseismic coupling on the subduction interface and upper plate deformation processes. Instead of the expected rifting signal we find strong contraction within the Taupo Volcanic Zone, indicating non-tectonic effects from magmatic and/or hydrothermal processes. Differences between S Hmax directions from historical seismicity (Townend et al.2012 ) and our maximum contraction directions demonstrate that at the Hikurangi margin historical seismicity and active faulting are strongly controlled by long-term processes, such as rotation of the forearc, rather than short-term, elastic strain from interseismic subduction interface locking.